2011
DOI: 10.1093/bja/aeq337
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ in inflammation and sepsis

Abstract: Nociceptin/orphanin FQ, N/OFQ, and its receptor NOP represent a non-opioid branch of the opioid superfamily that were first studied for their effects on pain responses. Both N/OFQ and NOP are involved in a wide range of 'non-pain' responses including immunomodulation and cardiovascular control. There is now growing interest in this system in inflammation and sepsis, which is the focus of this review article. The N/OFQ-NOP system is present in immune cells and N/OFQ modifies immunocyte function. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The effects of N/OFQ are not limited to the CNS. In peripheral tissues N/OFQ produces antitussive effects, negative chronotropic and ionotripic effects on heart, vasodilation, inhibition of gastrointestinal motility, inflammation, and sepsis (Lambert, 2008; Armstead, 2011; Leggett et al, 2009; Serrano-Gomez et al, 2011). However, at present a dearth of data from human clinical studies exists that have explored modification of these disease processes following manipulation of the N/OFQ system.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of N/OFQ are not limited to the CNS. In peripheral tissues N/OFQ produces antitussive effects, negative chronotropic and ionotripic effects on heart, vasodilation, inhibition of gastrointestinal motility, inflammation, and sepsis (Lambert, 2008; Armstead, 2011; Leggett et al, 2009; Serrano-Gomez et al, 2011). However, at present a dearth of data from human clinical studies exists that have explored modification of these disease processes following manipulation of the N/OFQ system.…”
Section: Introductionmentioning
confidence: 99%
“…That is, subsequent to the induction of sepsis by cecal ligation and puncture, OFQ/N administration to rats increased mortality, while NOP-R antagonist treatment attenuated various cellular and cytokine parameters of inflammation, and reduced mortality (Carvalho et al, 2008). Corresponding data in human clinical situations has been noted, with higher correlations of plasma OFQ/N in non-surviving septic patients suggesting that antagonism of OFQ/N may be a potential immunotherapeutic manipulation that may aid recovery (Serrano-Gomez et al, 2011). Overall, while little is known about the precise interactions between OFQ/N and the immune system, there is compelling evidence to explore this relationship further and elucidate the relevance of this to immunopathological and inflammatory disorders.…”
Section: Ofq/n and Inflammationmentioning
confidence: 81%
“…Both in vitro and in vivo studies have supported the evidence that NOP and nociceptin play a role in systemic inflammatory reactions and sepsis [11]. However, studies in humans have been conflictual: Decreased nociceptin plasma protein has been reported in fibromyalgia-syndrome patients compared to controls [9].…”
Section: Discussionmentioning
confidence: 94%